Relationship Between Spirituality and Resilience among Nursing Students of Mindanao State University-Iligan Institute of Technology during the COVID-19 Pandemic - E.COYOCA, GLORIA SHIELA; C. INTERINO, HEDAYA NISAH; P. MACADATO, ELHAM; D. MANALOCON, SITTIE SHAINA (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Studies have shown that the psychological well-being of nursing students during the pandemic is critical for their academic success and that spirituality has been a key aspect of fostering resilience and growth through challenging circumstances. This research is a descriptive correlational study that aimed to determine the correlation of the respondents’ demographic profile, their level of spirituality, and their level of resilience. The Spirituality and Resilience Assessment Packet by Kass and Kass (2000) was used to assess the respondents’ level of spirituality and resilience. Through an online form, the data was collected and was analyzed using descriptive statistics, Pearson’s correlation coefficient test, and T-test. Results of the study show that the respondents have a high level of spirituality and low level of resilience. Findings revealed that there is a positive linear correlation between spirituality and the respondents’ age and sex with females being more spiritually inclined than males and between resilience and the respondents’ age and year level. Moreover, results also revealed that there is a positive correlation between the respondents’ spirituality and their level of resilience. While this study offers insights into the important role of spirituality and resilience in helping nursing students during a pandemic, additional research is needed to further our understanding of the relationship between these two factors and their impact on health and well-being. Recommendations for future research might include expanding this study to a regional or national perspective.